HUBUNGAN KONSEP DIRI DENGAN KECERDASAN EMOSIONAL GURU TAMAN KANAK-KANAK DI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Renny Andria Yani Andria Yani; Zulkifli N, Zulkifli N, '; Devi Risma Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: This study has to purpose the correlation of the correlation of self concept and emotional intelligence kindergarten teacher in the Keritang district Indragiri Hilir regency. Population in this research were all kindergarten teacher in Keritang district a total of 35 people. Used the sample is saturated sample mean population is sampled. The collection of data technique is used questionnaire. Data analysis using descriptive analysis and correlation analysis product moment had tated previously assumptions. The result showed that there is a relationship between self concept and emotional intelligence. It is seen from r amounted 0,475.Keywords: self concept, emotional intelligence